Effect of ISM1 on the Immune Microenvironment and Epithelial-Mesenchymal Transition in Colorectal Cancer - Wu, Yuhui; Liang, Xiaojing; Ni, Junjie; Zhao, Rongjie; Shao, Shengpeng; Lu, Si; Han, Weidong; Yu, Liangliang (Frontiers in Cell and Developmental Biology, 2021)
Background: An increasing number of studies have shown that Isthmin1 (ISM1), a secreted protein, is important in tumorigenesis and invasion, including in colorectal cancer (CRC). However, the mechanisms are still unclear. This study aims to explore the function and prognosis capacity of ISM1 in CRC. Methods: We investigated the expression of ISM1 in 18 CRC tissues vs adjacent normal tissues from GSE50760, 473 CRC tissues vs 41 normal tissues from The Cancer Genome Atlas (TCGA), and across gastrointestinal cancer types. Differences were further confirmed in CRC tissues via quantitative real-time polymerase chain reaction (qRT-PCR). Then, we analyzed correlations between clinicopathologic features and ISM1 expression, including prognostic prediction value, using the Kaplan-Meier method and multivariate Cox regression. Gene set enrichment analysis (GSEA) was performed to identify ISM1-related pathways. In vitro experiments were performed to verify the role of ISM1 in epithelial-mesenchymal transition (EMT) and CRC progression. Results: Multiple datasets showed that ISM1 is upregulated in CRC tissues, which was validated. Patients with higher ISM1 expression had shorter overall survival (OS), and ISM1 expression served as an independent prognostic factor. Enrichment analysis showed that ISM1 upregulation was positively correlated with cancer-related pathways, such as EMT, hypoxia, and the Notch and KRAS signaling pathways. We were exclusively interested in the connection between ISM1 and EMT because 71% of genes in this pathway were significantly positively coexpressed with ISM1, which may account for why patients with higher ISM1 expression are prone to regional lymph node involvement and progression to advanced stages. In addition, we found that ISM1 was positively correlated with multiple immunosuppressive pathways such as IL2/STAT5, TNF-α/NF-κB and TGF-β, and immune checkpoints, including PD-L1, PD-1, CTLA-4 and LAG3, which may account for upregulation of ISM1 in anti-PD-1-resistant patients. Notably, through in vitro experiments, we found that ISM1 promoted EMT and colon cancer cell migration and proliferation. Conclusions: ISM1 is critical for CRC development and progression, which enhances our understanding of the low response rate of CRC to immunotherapy via immunosuppressive signaling pathways.